Echa prasowe aktywności ministrów oświaty Bułgarii, Szwecji i Węgier odwiedzających Polskę w 1935 r. - Gołdyn, Piotr (Biuletyn Historii Wychowania, 2014)
The renascent Polish state was being built in the interwar period (1918-1939), developing its position on all possible levels in the international arena. One of these was education and culture. Poland signed a lot of international agreements in this field. This was connected with visits by our ministerial representatives to other countries and with arranging visits in Poland for guests from different countries. In 1935 three ministers of education from abroad visited Poland: Teodor Radew (Bulgaria), Artur Engberg (Sweden) and Balaint Homan (Hungary). The visit of the first two ministers was connected with the signing of a Polish-Bulgarian and Polish-Swiss cultural agreement. The Hungarian minister of education came to Poland to assess the implementation of the agreement which had been signed between Poland and Hungary a year before. While staying in Poland, beside official meetings with the president and the ministers of education and foreign affairs, our guests visited different educational institutions in cities such as Warsaw, Krakow, Poznan or Vilnius. The press took a lively interest in those visits, reporting them on an ongoing basis. Apart from news reports, editorials and even articles appeared. These were devoted to some of the educational and cultural issues of our guests’ countries.